2002
DOI: 10.1176/appi.ajp.159.12.2000
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Deformities in Schizophrenia Characterized by High Dimensional Brain Mapping

Abstract: Schizophrenia is associated with structural deformities of the hippocampus, which suggest a disturbance of the connections between the hippocampus and the frontal cortex. However, the magnitude of these deformities are not related to severity or duration of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
165
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 49 publications
17
165
1
1
Order By: Relevance
“…In line with a recent study that reported greater hippocampal shape alterations in patients with schizophrenia and prior comorbid alcohol use disorders (Smith et al, 2011), we hypothesised that cannabis use would exert an additional effect on the hippocampal pathology typically observed in schizophrenia, particularly in the anterior hippocampus (Csernansky et al, 2002;Small et al, 2011;Tamminga et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
“…In line with a recent study that reported greater hippocampal shape alterations in patients with schizophrenia and prior comorbid alcohol use disorders (Smith et al, 2011), we hypothesised that cannabis use would exert an additional effect on the hippocampal pathology typically observed in schizophrenia, particularly in the anterior hippocampus (Csernansky et al, 2002;Small et al, 2011;Tamminga et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
“…Previously we also found a general lack of correlation of volume or shape measures with clinical symptoms or cognitive function in the thalamus, hippocampus, and basal ganglia (Csernansky et al, 2002(Csernansky et al, , 2004Andrews et al, 2006;Mamah et al, 2007). An absence of correlation between thalamic volume and clinical measures has also been reported in other studies (Gilbert et al, 2001;Ettinger et al, 2007).…”
Section: Discussionmentioning
confidence: 79%
“…Several in vivo imaging and postmortem studies have failed to find abnormalities in thalamic volume or neuronal number in schizophrenic subjects (Portas et al, 1998;Arciniegas et al, 1999;Deicken et al, 2002;Cullen et al, 2003;Dorph-Petersen et al, 2004;Preuss et al, 2005). Moreover, recent neuroimaging analyses of the hippocampus (Csernansky et al, 2002) and thalamus (Csernansky et al, 2004) in the same cohort of schizophrenic subjects has indicated that pathology of one or the other structure may be more pronounced in different individuals (Csernansky, personal communication).…”
Section: Comparable Cell Number In Schizophrenic and Control Subjectsmentioning
confidence: 99%